A novel state–space model reference adaptive speed control design for fractional-order model-based wind turbine - Mohammed Islam Leulmi; Samir Ladaci; Horst Schulte (International Journal of Electrical Power & Energy Systems, 2025)
Fractional-order adaptive control has recently emerged as an effective solution for controlling processes whose model is unknown or varies slowly over time. It has been shown that using fractional operators in the control system can add a greater degree of robustness against noise and disturbances. Among the most popular fractional order controllers, fractional-order model reference adaptive control (FOMRAC) has proven to be able to improve the plant dynamics and to enhance temporal performance like rise time, response time and robustness against disturbances and noises. It augments also the stability margin relatively to standard adaptive control by reducing the adaptive gain values.This paper presents a new FOMRAC design for controlling the wind turbine rotor speed based on a fractional-order approach. First of all, a state–space fractional-order model is proposed to describe the wind turbine. Then, the proposed FOMRAC algorithm continuously updates the controller parameters to force the closed-loop wind turbine system to behave as a chosen reference model. The stability analysis of the resulting adaptive fractional order control system is performed based on Lyapunov theory. Numerical simulation results and a comparative study versus a PSO-based PID controller illustrate the effectiveness and the advancement of the presented controller compared to standard solutions.